A randomized phase II clinical trial of dendritic cell vaccination following complete resection of colon cancer liver metastasis. Issue 1 (29th September 2018) - Rodriguez, Javier; Castañón, Eduardo; Perez-Gracia, Jose Luis; Rodriguez, Inmaculada; Viudez, Antonio; Alfaro, Carlos; Oñate, Carmen; Perez, Guiomar; Rotellar, Fernando; Inogés, Susana; López-Diaz de Cerio, Ascensión; Resano, Leyre; et al.
Abstract : Surgically resectable synchronic and metachronic liver metastases of colon cancer have high risk of relapse in spite of standard-of-care neoadjuvant and adjuvant chemotherapy regimens. Dendritic cell vaccines loaded with autologous tumor lysates were tested for their potential to avoid or delay disease relapses (NCT01348256 ). Patients with surgically amenable liver metastasis of colon adenocarcinoma ( n  = 19) were included and underwent neoadjuvant chemotherapy, surgery and adjuvant chemotherapy. Fifteen patients with disease-free resection margins were randomized 1:1 to receive two courses of four daily doses of dendritic cell intradermal vaccinations versus observation. The trial had been originally designed to include 56 patients but was curtailed due to budgetary restrictions. Follow-up of the patients indicates a clear tendency to fewer and later relapses in the vaccine arm (median disease free survival –DFS-) 25.26 months, 95% CI 8.74-n.r) versus observation arm (median DFS 9.53 months, 95% CI 5.32–18.88).